FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS PENGELOLAAN DANA DESA (STUDI KASUS KALURAHAN DENGAN IDM PREDIKAT MANDIRI DI KABUPATEN SLEMAN) - Vidya Vitta Adhivinna; Raafi Astrian Yudhistira; Ratna Purnama Sari; Rahandhika Ivan Adyaksana (JURNAL FAIRNESS, 2024)
This study aims to test and obtain empirical evidence of the positive effect of transparency, the quality of village apparatus on the accountability of village fund management. This study uses primary data in the form of a survey by distributing questionnaires directly to 44 villages that received IDM with 352 respondents. The sampling technique used was purposive sampling technique with criteria based on Permendagri No. 20 of 2018. The data testing method is descriptive statistical test, data quality test, and hypothesis testing. The results of this study indicate that transparency, the quality of village officials, and the government's internal control system have a significant effect on the accountability of village fund management